Compact 0.7 mJ/11 ns eye-safe erbium laser. (16th November 2016) - Vitkin, V V; Polyakov, V M; Kharitonov, A A; Buchenkov, V A; Rodionov, A Yu; Zhilin, A A; Dymshits, O S; Loiko, P A
Abstract: We report on the development of a compact diode-end-pumped eye-safe (~1.54 µ m) passively-cooled Er, Yb:glass laser. The design of this laser is facilitated by the use of a double-pass pumping scheme and a special ZrO2 diffuse reflector for a uniform pump distribution. In the free-running mode, this laser generates 8.2 mJ/3 ms pulses with a slope efficiency of 15%. Passive Q-switching is provided by saturable absorbers made of transparent glass-ceramics containing Co 2+ : γ -Ga2 O3 or Co 2+ :MgAl2 O4 nanocrystals with a spinel structure. In the latter case, 0.7 mJ/10.5 ns pulses are generated corresponding to  >60 kW peak power and good beam quality ( M 2   =  1.4). The designed laser is suitable for portable range-finders.